2018
DOI: 10.3844/ajassp.2018.182.185
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Age and Dental Age Using Demirjian in Down Syndrome Children

Abstract: Down syndrome is a chromosomal abnormality (trisomy 21) characterized by an extra chromosome 21. People with Down syndrome have impairement in mental and physical development, including delayed dental development. Dental age is stage of development of teeth measured by maturation stage of teeth. This study aims to determine or asses the growth or maturation of permanent teeth in children with Down syndrome. This research was a cross-sectional analysis. Analysis test using paired t-test to compare the average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Further investigation of skeletal maturation among Down syndrome individuals has become necessary as various authors have reported different rate of maturation in these individuals. 9,[10][11][12][13][14][15][25][26][27][28] The acceleration in the rate of growth at 12 years of age and early attainment of maturity at 15 years of age as observed in this present study is suggestive of a short period of active growth among Down syndrome male individuals, and this corroborates the findings of De Moraes et al 9 Orthodontic treatment for these individuals should therefore be properly timed to avoid missing the short window of active skeletal growth among Down syndrome male individuals. Also, advanced skeletal maturation observed among male Down syndrome individuals at 15 in this current study is similar to the findings reported by Sannomiya et al 8 The outcomes of this present study further emphasized the influence of assessment techniques on the outcome of skeletal maturation determination.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further investigation of skeletal maturation among Down syndrome individuals has become necessary as various authors have reported different rate of maturation in these individuals. 9,[10][11][12][13][14][15][25][26][27][28] The acceleration in the rate of growth at 12 years of age and early attainment of maturity at 15 years of age as observed in this present study is suggestive of a short period of active growth among Down syndrome male individuals, and this corroborates the findings of De Moraes et al 9 Orthodontic treatment for these individuals should therefore be properly timed to avoid missing the short window of active skeletal growth among Down syndrome male individuals. Also, advanced skeletal maturation observed among male Down syndrome individuals at 15 in this current study is similar to the findings reported by Sannomiya et al 8 The outcomes of this present study further emphasized the influence of assessment techniques on the outcome of skeletal maturation determination.…”
Section: Discussionsupporting
confidence: 89%
“…[30][31][32] Although this present study also observed a tendency to exhibit delay in skeletal maturation among Down syndrome individuals, the differences observed in this present study were however not significant as against the significant delay in the dental calcification stages observed in the studies conducted by other authors. 25,28 The different methodology and sample population in the studies 25,28 and this present study could have accounted for the differences observed.…”
Section: Discussionmentioning
confidence: 76%
“…There were 14 studies found from the conducted search, which summarized in Table 1. The age coverage of the most study was young adult and children (71%) [11][12][13][14][15][16][17][18][19][20] . Only three studies which involved age range more than 25 years [21][22][23] .…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
“…The age's range and sample options are related to which age estimation method should be used in the studies. The most age estimation method applied in Indonesian population was Demirjian's method, with or without modification (35.71%) 11,12,15,16,21 , followed by TCI-Benindra's method (21.42%) [18][19][20] , and the other methods (7.14%-13%), as presented in Figure 1. Panoramic radiograph was the most used sample for the studies (53%) 11,12,[15][16][17][18][19][20][21]23 , followed by clinical examination (17%) 13,14,24 , periapical radiograph (12%) 18,19 , lateral cephalometric radiograph (12%) 18,19 , and CBCT (6%) 22 (Figure 2).…”
Section: Dental Age Estimation In Indonesian Populationmentioning
confidence: 99%
“…Disorders that also include in condition disabled since born as mental retardation, difference physique certain as shape little face flat and rising a number of risk on condition medical including disturbance hearing loss hyroid disorder channel digestibility, and visual damage ( Pramidi , Gartika , and Soewondo 2019). According to Nawawi, Gartika , and Soewondo (2018) children with DS other than experience mental and physical health disorders , also experience growth delayed teeth .…”
Section: Introductionmentioning
confidence: 99%